"And what of my Onegin?" Displacement and Reinvention of the Hero in Eugene Onegin. Issue 1 (16th January 2013) - DVIGUBSKI, ANNA
<x xml:space="preserve">Abstract</x> In discussions of Eugene Onegin, the role of the author‐narrator often presents particular difficulty. Critics have tried to explain the contradictions underlying Pushkin's construction of this character, which appears to occupy simultaneously a fictional and a biographical plane in the work. In this paper, I propose an interpretation of this figure as a competitor to Onegin for the status of the hero. I argue that by including the author‐narrator in the work, Pushkin challenges the genre conventions of the romantic poem, first distancing and parodying the Romantic hero Eugene and then replacing him with the author‐narrator who represents a new kind of hero. Parallel to this experimentation with genre conventions is Pushkin's interest in reshaping the Russian literary language. As Onegin is succeeded by the author‐narrator as the hero, the Russian poetic conventions of Pushkin's time are similarly distanced and replaced by Pushkin's (and the author‐narrator's) verbal inventions. Finally, I suggest that the author‐narrator is an example of a new complex consciousness, specifically in his ability to recreate the voices of other poets in contrast to his own poetic discourse, which shows a movement in the direction of the Russian realist novel, specifically Dostoevsky's polyphonic model of consciousness.